Knowledge and practice on menstrual hygiene among adolescent girls of selected slums in Kathmandu valley (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Hygiene related practices during menstruationare of considerable importance. This study assesses the existing level of knowledge on menstrual hygiene, and its compliance, among adolescent girls of selected slum areas in Kathmandu, Nepal.Methods: Descriptive cross sectional study design was applied and slums in Kathmandu district were selected conveniently as research site. Primary data were collected through interview by using structured questionnaire. The association between knowledge and practices were identified through chi square test.Results: There were282 respondents for study. Less than half 121 (42.9%) had adequate knowledge related to menstruation and its hygiene. Two-third 185(65.6%) of the participants used sanitary pads, 183 (98.9%), washed hands after pad change, 271 (96.1%) cleaned perineal area during menstruation, 227(80.5%) were aware about the myth and 61.9% followed social norms and restriction related with menstruation. Age of the participant, their education level and the income sources were found statistically significant with their level of knowledge on menstruation.Conclusions: More than half of adolescent girls of slums in Kathmandu district had inadequate knowledge regarding menstruation and two-third practiced menstrual hygiene.